2020
DOI: 10.15376/biores.15.3.6244-6261
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase activity and melanogenic effects of Lespedeza bicolor extract in vitro and in vivo

Abstract: Lespedeza bicolor (L. bicolor) is used for medicinal purposes because of its various biological and pharmacological activities. In this study, the effects of L. bicolor ethanol extract on the treatment of vitiligo were investigated. The determination of melanin content in melanocytes was measured using B16 melanoma cells and C57BL/6J Ler-vit/vit mice. Finally, the quercetin content in L. bicolor were qualitatively analyzed using HPLC. The results obviously indicated that the L. bicolor extract enhanced melanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Lespedeza bicolor extract applied at an amount of 0.2 mL/cm 2 to those animals significantly increase the level of melanocytes in the skin. The main constituent of extract was identified as quercetin [ 112 ]. Application of 0.2 mL/cm 2 Rhododendron schlippenbachii extract for 5 months leads to melanin production [ 113 ].…”
Section: The Effect Of Plant Extracts and Pure Compounds On Melanin C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lespedeza bicolor extract applied at an amount of 0.2 mL/cm 2 to those animals significantly increase the level of melanocytes in the skin. The main constituent of extract was identified as quercetin [ 112 ]. Application of 0.2 mL/cm 2 Rhododendron schlippenbachii extract for 5 months leads to melanin production [ 113 ].…”
Section: The Effect Of Plant Extracts and Pure Compounds On Melanin C...mentioning
confidence: 99%
“…It was revealed that Cyrtomium fortunei [ 109 ], Panax ginseng [ 116 ], Artocarpus chama [ 72 ] and Punica granatum [ 124 ] extracts suppress cellular melanogenesis. Lespedeza bicolor [ 112 ] and Rhododendron schlippenbachii [ 113 ] extracts show the opposite effect. Rosa gallica and Aster yomena extracts evoke skin whitening by modulation of MAPKs [ 126 ] and ERK and AKT [ 130 ] signaling.…”
Section: In Vitro Studiesmentioning
confidence: 99%